Practical Synthesis of 3-Oxa-6-azabicyclo[3.1.1]heptane Hydrotosylate; A Novel Morpholine-Based Building Block - Walker, Daniel P.; Eklov, Brian M.; Bedore, Matthew W. (Synthesis, 2012)
Bridged bicyclic morpholines are important building blocks in medicinal chemistry research. The bicyclic morpholine 3-oxa-6-azabicylo[3.1.1]heptane (3a) is of particular interest as a morpholine isostere because it is achiral and shows similar lipophilicity to that of morpholine, based on the cLogP of a derived analogue. The first synthesis of morpholine 3a (tosylate salt) is described; the seven-step sequence begins with inexpensive starting materials and uses straightforward chemistry.
Keywords: isosteres; bicyclic compounds; heterocycles; cyclization; medicinal chemistry